Reorganization Outcomes of the Ministry of Public Health in 2002 Related to AIDS Control and Prevention - Ukachoke, Kitiya (Journal of Health Science of Thailand, 2018)
This cross-sectional survey study had objectives of comparing manpower management, budgeting process, working structure on AIDS control and prevention programs before and after the reorganization of the Ministry of Public Health (MOPH) in 2002. In addition, the study also explored the impact of the reorganization to AIDS control and prevention programs in the provincial areas. The study collected and analyzed data from questionnaires that were sent to and responded back from provincial public-health offices across the nation in November 2007. Prior to the reorganization in 2002, AIDS control and prevention programs were under the responsibility of the Venereal Diseases and AIDS Control and Prevention Division. After the reorganization, this responsibility has been transferred to the General Infectious Control Division. Five to eight staffers in each working unit before the reorganization were reduced to three afterward. It was found that the advantages of the reorganization were the opportunity to integrate resources, the better definition of the working procedures, the more compact but effective working units, the safer and more satisfactory services. On the contrary, the disadvantages were the lack of experienced veterans keen on innovations, decrease of the number of personals, decrease of the budget, and the most important issue was the transfer of venereal clinics from provincial health offices to provincial hospitals. After the reorganization, the budget decreased but integration became more pronounced. The locals had opportunities to participate and were able to be more involved with their own community problems. However, the budget was reduced to the point that it was insufficient to venture into innovations. Concerning the impact of the involvement of the National Health Security Office (NHSO), it was found that the advantages were additional financial sources for AIDS control and prevention and accessibility to the service. Nevertheless, this financial support was devoted mainly to AIDS treatment. Moreover, the working units expressed their opinions on the reorganization of MOPH in 2002 in important issue that there should have been proper criteria on minimum manpower requirement. MOPH should have empowered the local authorities in AIDS control and prevention prior to the reorganization. There should have focused on reorientation and capacity building on comprehension of issues and upcoming changes.There should be coordination with NHSO in order to increase budget support for AIDS control and prevention and the budget should have not emphasized only on expenses on antiretroviral drugs prescribed to HIV infected/AIDS patients. Also, there should have been an evaluation of the present working structure whether there were any hindrances and what degree of success it has attained in AIDS control and prevention after the reorganization